2012
DOI: 10.1017/s0950268812000994
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiological investigation of a Legionnaires' disease outbreak in Christchurch, New Zealand: the value of spatial methods for practical public health

Abstract: SUMMARYBetween April and August 2005 Christchurch, New Zealand experienced an outbreak of Legionnaires' disease. There were 19 laboratory-confirmed case including three deaths.Legionella pneumophilaserogroup 1 (Lpsg1) was identified as the causative agent for all cases. A case-control study indicated a geographical association between the cases but no specific common exposures. Rapid spatial epidemiological investigation confirmed the association and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Different molecular markers have been used to characterize Legionella populations in previous genetic studies (6), but sequence-based typing (SBT) has become the current gold-standard typing tool (7,8). Apart from its utility in epidemiological investigations of LD outbreaks (9)(10)(11), SBT provides nucleotide sequence data that can be used for further analyses of genetic variability and population structure (12,13). A recent study has shown that even though undetected genomic variability within sequence types (ST) could mislead the identification of Legionella reservoirs during outbreak investigations, genetic distances determined by using SBT data correlate significantly with genome-wide estimates (14).…”
mentioning
confidence: 99%
“…Different molecular markers have been used to characterize Legionella populations in previous genetic studies (6), but sequence-based typing (SBT) has become the current gold-standard typing tool (7,8). Apart from its utility in epidemiological investigations of LD outbreaks (9)(10)(11), SBT provides nucleotide sequence data that can be used for further analyses of genetic variability and population structure (12,13). A recent study has shown that even though undetected genomic variability within sequence types (ST) could mislead the identification of Legionella reservoirs during outbreak investigations, genetic distances determined by using SBT data correlate significantly with genome-wide estimates (14).…”
mentioning
confidence: 99%
“…For example, in an outbreak of Legionnaires' disease in Christchurch, New Zealand, cases were identified at a distance of 12 km from the implicated cooling tower [38]. White and colleagues therefore proposed updates to World Health Organization guidelines which at the time placed the area at risk from such sources at 3.2 km.…”
Section: Comparing Results With Established Factsmentioning
confidence: 99%
“…Although the simple dot map was the most commonly used method, a wide range of techniques were applied, including more sophisticated data visualisations and analytic tools. Across the range of studies, there were examples of spatial tools being usefully applied throughout the course of an outbreak investigation; from initial confirmation of the outbreak to describing and analysing [11,18-28,30-36,38,40-50,55,56,58-60, 63,67-69,71-76,80,82-85,87-93,96-105] Thematic map 25 [18,19,[21][22][23]28,29,38,41,42,45,46,50,60,68,70,74,80,82,89,91,[93][94][95]103] Rate map 14 [20,30,44,45,49,50,57,63,70,76,79,81,90,101] Smoothed incidence map 13 [11,31,[48][49][50]73,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Legionella detection in sputum as well as in water samples plays a critical role in public health. Thus, identifying Legionella as the causative agent of infection is crucial for disease treatment and outbreak prevention3351.…”
Section: Discussionmentioning
confidence: 99%